Dampak Pernikahan Dini dan Problematika Hukumnya - Julijanto, Muhammad (Jurnal Pendidikan Ilmu Sosial, 2015)
The article talks over about early married effects and its lawproblematic in Indonesia. Married is the right of everybody.Human being instinct to continue married civilization is to be thekeywords of culture improvement in one nation. Married can bebasic of doing better social effort. The qualified Family buildingwill produce excellent generation in one nation. In the other hand, family failurewill give effect to the society bankruptcy and fail in preparing excellentgeneration. The psychology effect will influence the growing up children in thefuture. Early married is as social problem that is caused by many factors, such as;free sex impact, demoralized and bad attitude of young generation. Early marriedimpact caused the quality of house hold is not excellent, both in reproductionhealth, or in preparation psychology and family economic, therefore it bringsdivorce effect, and unmanaged the quality of children education.